THE INFLUENCE OF LEADERSHIP COMPETENCIES, STAKEHOLDER PARTICIPATION, AND TECHNOLOGY UTILIZATION ON EDUCATION QUALITY WITH DIGITAL TRANSFORMATION AS AN INTERVENING VARIABLE - Rahayu, Olivia; Suhardi; Hamdan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This quantitative research analyzes the influence of leadership competencies, stakeholder participation, and technology utilization on the quality of education through the mediation of digital transformation at the basic education level of Pangkalpinang City. Using Structural Equation Modelling (SEM) with 206 respondents including principals, teachers, parents/guardians, administrative and IT staff, representatives of the Education Office, and academics, the results show that digital transformation has a dominant influence on the quality of education, indicating the crucial role of technology in improving the efficiency, inclusivity, and personalization of learning. Leadership competencies have a significant direct impact, even though their integration with digitalization is not optimal. The use of technology has a direct and indirect effect through digital transformation, while stakeholder participation strengthens the quality of education indirectly through digitalization. The SEM model emphasizes that improving the quality of education requires synergy between visionary leadership, adaptive technology, and integrated stakeholder participation in the digital ecosystem. These findings recommend policy development that focuses on digital capacity building, technology-based leadership training, and multi-stakeholder collaboration to address disparities in access to and quality of education